TAFSIR EMANSIPATORIS: PEMBUMIAN METODOLOGI TAFSIR PEMBEBASAN - Fatkhul Mubin (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
This paper aims to describe the emancipatory methodology of interpretation as a method of interpreting the Qur'an that is responsive to socio-cultural conditions and not trapped in the ideological-dogmatic confines of reasoning. This is because the discourse of interpretation is still enlivened by the interpretation which is still focused on the relation of the text to the interpreter only, so that the socio-cultural locus has not been touched, instead of solving social problems based on text. This type of research is library research with a descriptive analysis approach. Data sources in the study are divided into two types, namely: primary in the form of scholarly work that discusses emancipatory interpretation and secondary in the form of books and scientific works related to the science and interpretation of the Qur'an. This research concludes that the emancipatory interpretation treats the text of the scriptures in a space of critical reflection as well as being applied in the realm of praxis, not only morally but also structurally. Here, the text of the scriptures is used as a tool to sharpen conscience in seeing, perceiving and at the same time solving social problems of humanity. The principle of interpretation of scriptural texts, here linguistically, must be comprehensive and philosophical. And in the context of praxis, the text of the scriptures ethically liberation must be reflected in the lives of humanity.